2022
DOI: 10.21203/rs.3.rs-2368740/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity, population genetic structure and gene flow in the rare and endangered wild plant Cypripedium macranthos revealed by genotyping-by-sequencing

Abstract: Background: Genetic diversity, genetic structure, and gene flow in plant populations and their influencing factors are important in conservation biology. Cypripedium macranthos isone of the few wild orchids with high ornamental value in northern China. However, over the past decade, excessive collection, trading, tourism development, habitat fragmentation, deceptive pollination, and seed germination difficulties have all caused a sharp decline in the number of C. macranthos individuals and its population. In o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(39 reference statements)
0
1
1
Order By: Relevance
“…Phaius avus (Pi = 1.439 × 10 − 4 , Ho = 0.788, He = 0.707) from the BM population exhibited a higher level of genetic diversity. This is in contrast to other orchids such as Cypripedium macranthos (Pi = 0.154, Ho = 0.134, He = 0.153) [13], Geodorum eulophioides (Pi = 0.158, Ho = 0.012, He = 0.025) [18], and D. catenatum (Pi = 0.158, Ho = 0.099, He = 0.158) [29]. Similarly, P. avus from the BM population showed signi cant genetic diversity compared to congeneric Phaius such as P. australis and P. bernaysii [20].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Phaius avus (Pi = 1.439 × 10 − 4 , Ho = 0.788, He = 0.707) from the BM population exhibited a higher level of genetic diversity. This is in contrast to other orchids such as Cypripedium macranthos (Pi = 0.154, Ho = 0.134, He = 0.153) [13], Geodorum eulophioides (Pi = 0.158, Ho = 0.012, He = 0.025) [18], and D. catenatum (Pi = 0.158, Ho = 0.099, He = 0.158) [29]. Similarly, P. avus from the BM population showed signi cant genetic diversity compared to congeneric Phaius such as P. australis and P. bernaysii [20].…”
Section: Discussioncontrasting
confidence: 66%
“…Roads have played a crucial role in human activities throughout the agricultural development and urbanization process, negatively impacting the genetic diversity and differentiation of wild plant populations [9], by reducing plant diversity and limiting certain species [10]. Orchids, one of the most sensitive plants in nature, suffer from habitat fragmentation due to indiscriminate mining and overexploitation [11][12][13], resulting in changes in their genetic structure and reduced genetic diversity. An evaluation of 653 orchid species in China revealed that 65% of these species face challenges related to habitat fragmentation [14].…”
Section: Introductionmentioning
confidence: 99%